2013
DOI: 10.1007/s10198-013-0547-3
|View full text |Cite
|
Sign up to set email alerts
|

Demand uncertainty and hospital costs: an application to Portuguese public hospitals

Abstract: In this paper, we evaluate the effect of demand uncertainty on hospital costs. Since hospital managers want to minimize the probability of not having enough capacity to satisfy demand, and since demand is uncertain, hospitals have to build excess capacity and incur the associated costs. Using panel data comprising information for 43 Portuguese public hospitals for the period 2007-2009, we estimate a translog cost function that relates total variable costs to the usual variables (outputs, the price of inputs, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The predictability of hospital demand is another factor to consider when examining how the UrD is related to hospitals' efficiency. Prior research has found that higher demand uncertainty, defined by the difference between predicted and actual demand for emergency treatment, has detrimental effects on performance, because hospitals have to maintain resources that are ultimately used inefficiently or not at all [1,16]. This line of reasoning might also be applicable to our findings in that hospitals facing demand uncertainty due to higher UrD might be struggling with resource optimization.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The predictability of hospital demand is another factor to consider when examining how the UrD is related to hospitals' efficiency. Prior research has found that higher demand uncertainty, defined by the difference between predicted and actual demand for emergency treatment, has detrimental effects on performance, because hospitals have to maintain resources that are ultimately used inefficiently or not at all [1,16]. This line of reasoning might also be applicable to our findings in that hospitals facing demand uncertainty due to higher UrD might be struggling with resource optimization.…”
Section: Discussionmentioning
confidence: 51%
“…More specifically, the unpredictability of medical urgencies makes it difficult to optimize the planning and use of resources [6]. Indeed, prior research has shown that hospitals respond to demand uncertainty by changing their cost structure and production [1,15], which might, in turn, also lead to inefficiencies because more standby capacity needs to be maintained causing a higher risk that this capacity will remain unused [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of using panel data that comprises information for 43 Portuguese National Health Service (NHS) hospitals for the period 2007 to 2009 [44] indicated that for most of their samples, hospitals that face higher urgent demand have higher cost. In other words, as the percentage of urgent demand increases, the total cost increases at an increasing rate.…”
Section: Percent Urgent Demand (Pu) Under Different Policies (Mp CDmentioning
confidence: 99%
“…Gittell et al (2000) argue that the level of uncertainty they experience may be much higher than in manufacturing organizations. This uncertainty can lead to excess capacity and higher costs (Almeida and Cima 2015).…”
Section: Introductionmentioning
confidence: 99%